Dampak Kualitas Pelayanan, Kualitas Produk, dan Harga terhadap Kepuasan Pelanggan pada Alfamart Penfui Timur, di Kabupaten Kupang, Nusa Tenggara Timur - Sarlianus Poma (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2025)
The purpose of the research is to examine how customer satisfaction at Alfamart, East Penfui, Kupang Regency, East Nusa Tenggara, is impacted by service quality, product quality, and pricing. The sampling method used is purposive sampling method, namely a technique where the sample is determined on the basis of criteria or considerations. The studys findings demonstrated that product quality had no significant and partially impact on customer satisfaction at Alfamart, while service quality and price had a partially positive and large impact. At Alfamart, customer satisfaction was positively and significantly impacted by pricing, product quality, and service quality all at the same time. This study employed a quantitative approach. A questionnaire served as the instrument, and multiple regression was the method of data analysis. Customer satisfaction was significantly and favorably impacted by the regression coefficient test results for pricing, product quality, and service quality taken combined.